Clinical impact of gastroesophageal reflux disease in patients with subacute/chronic cough - Yoshihiro Kanemitsu; Ryota Kurokawa; Norihisa Takeda; Masaya Takemura; Kensuke Fukumitsu; Takamitsu Asano; Jennifer Yap; Motohiko Suzuki; Satoshi Fukuda; Hirotsugu Ohkubo; Ken Maeno; Yutaka Ito; et al. (Allergology International, 2019)
Background: While gastroesophageal reflux disease (GERD) is one of the commonest causes of subacute/chronic cough along with cough-variant asthma (CVA) and rhinosinusitis, its clinical impact remains unknown. Therefore, we sought to investigate the impact of GERD in patients with subacute/chronic cough. Methods: Between April 2012 and March 2018, a total of 312 patients presenting subacute or chronic cough lasting for ≥3 weeks [median cough duration, 4.9 (0.7–434) months] underwent diagnostic tests. GERD symptoms and cough-specific QoL were evaluated through the Frequency Scale for Symptoms of Gastroesophageal reflux (FSSG) and the Japanese version of the Leicester Cough Questionnaire (J-LCQ). According to the FSSG domains, patients with GERD were arbitrarily categorized into 3 groups; acid-reflux predominant, dysmotility predominant, and pauci-symptoms groups, respectively. Results: The average scores of J-LCQ was 12.5 (SD3.7). One hundred-forty three were diagnosed as having GERD-related cough based on classical reflux symptoms including heartburn and characteristic triggers of cough such as phonation, rinsing, lying, and eating. Most of them (89.8%) had other causative diseases including CVA. Cough lasted longer (p = 0.019) and required a longer time until alleviation (p = 0.003) in patients with GERD than in those without GERD. They also scored lower J-LCQ than counterpart group (p < 0.0001). In terms of symptom stratification, dysmotility predominant group showed significant more response to specific GERD treatments than the remnants (p = 0.002). Conclusions: These results indicate that GERD is associated with the aggravation of other causes including CVA. Particularly, dysmotility symptoms may be potential therapeutic target for GERD-related cough. Keywords: Cough-specific quality of life, Gastroesophageal reflux disease, GERD symptoms, Prokinetic agents, Subacute/chronic cough